Analisis Faktor Sosiologis terhadap Kepatuhan Pembayaran Iuran Peserta BPJS Kesehatan di Indonesia - Mochammad Abizar Yusro; Muhammad Aliefuddin Sayyaf; Thufail Rozaan (Jurnal Hukum Lex Generalis, 2021)
From the 32 million Healthcare and Social Security Agency (BPJS Kesehatan) participants, only 16 million participants are compliant to pay. This condition has a negative impact on the financial condition of BPJS Kesehatan which continues to experience deficits, one of which is due to the low number of independent participants to pay contributions. According to Soerjono Soekanto, there are four factors that affect law enforcement in society, namely: 1. The law and its own rules; 2. Adequate law enforcement facilities; 3. Awareness and Legal Certainty as well as community behavior; 4. Law enforcement mental apparatus. Reviewing the existing indicators on the fundamental problem that is the cause of the low level of independent participants in paying contributions is the participants' low legal awareness.